Two-Stage Mucogingival Surgery with Free Gingival Autograft and Biomend Membrane and Coronally Advanced Flap in Treatment of Class III Millers Recession - Avita Rath; Smrithi Varma; Renny Paul (Case Reports in Dentistry)
Introduction. Gingival recession is an apical shift of the gingival margin with exposure of the root surface. This migration of the marginal tissue leads to esthetic concerns, dentin hypersensitivity, root caries, and cervical wear. It is, paradoxically, a common finding in patients with a high standard of oral hygiene, as well as in periodontally untreated populations with poor oral hygiene. Changing the topography of the marginal soft tissue in order to facilitate plaque control is a common indication for root coverage procedures and forms a major aspect of periodontal plastic surgeries. The regeneration of a new connective tissue attachment to denuded root surface is by allowing the selective coronal regrowth of periodontal ligament cells while excluding the gingival tissues from the root during wound healing by means of a barrier membrane. Case Presentation. This case reports a two-stage surgical technique for treatment of Miller’s class III defect using free gingival autograft and type I absorbable collagen membrane (BioMend®, Zimmer Dental, USA)§. Conclusions. The 6-month follow-up of the case showed a significant increase in attached gingiva suggesting it as a predictable alternative in the treatment of Millers class III defects.